Examining the Relationship Between the Internet Addiction Levels of Licensed Athletes and Their Mental Toughness in Sports - Dogan, Ufuk; Gulen, Salih; Celik, Fatih (Turkish Green Crescent Soc, 2022)
In this study, the relationship between internet addiction levels and mental toughness levels of athletes who are actively engaged in licensed sports was examined. This descriptive study was conducted with 440 elite athletes in 2021. The Participant Descriptive Form, Internet Addiction Scale, and Sport Mental Toughness Questionnaire were used. In the analysis of data, statistical techniques such as the t-test, one-way analysis of variance, Pearson correlation were used with Statistical Package for Social Sciences 23.0. The mean Internet Addiction Scale score was 38.16 +/- 14.7, and the mean Sport Mental Toughness Questionnaire score was 2.86 +/- 0.35. A correlation was found between the duration of internet usage, the purpose of use, the tool used, and the age of the participants with their Internet Addiction Scale total scores. A low and significant negative correlation was found between Internet Addiction Scale and Sport Mental Toughness Questionnaire scores. It can be thought that if internet addiction is not intervened in athletes, mental toughness will decrease and, naturally, failure in sports may increase.
Keywords: Addiction; internet addiction; mental toughness; screen exposure; sports